2012
DOI: 10.4067/s0718-27242012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Small Companies Innovations in Emerging Countries: E-Business Adoption and its Business Model

Abstract: Organizations have been taking advantage of e-business as an innovative opportunity to improve business results, but small companies have not been adopting this tool as quickly as large corporations. There are several studies on the adoption of e-business in developed countries, but there are fewer studies in emerging Latin American countries. Thus, the goal of this study was to describe the business model of small companies that have adopted e-business (an innovation to this segment) in an emerging Latin Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Based on inductive theory building with a comparative case study, the authors find that latecomer firms, though disadvantaged in technological capabilities and market resources, can successfully introduce disruptive technologies from advanced economies into emerging economies through secondary business-model innovations [31]. Basing on EBMO, Novaes Zilber et al (2012) described the business model of small companies that have adopted e-business in an emerging Latin American country and found that the owners/shareholders play a central role in making decisions about the adoption of e-business as well as the main value delivered from using the internet was improved brand and/or product awareness [32]. Using EBMO, Kiani et al (2009) proposed causal loop diagram (CLD) and use it as a useful tool to capture the structure of e-business systems in order to achieve a better understanding of an e-business model.…”
Section: E-business Model Ontology (Ebmo)mentioning
confidence: 99%
“…Based on inductive theory building with a comparative case study, the authors find that latecomer firms, though disadvantaged in technological capabilities and market resources, can successfully introduce disruptive technologies from advanced economies into emerging economies through secondary business-model innovations [31]. Basing on EBMO, Novaes Zilber et al (2012) described the business model of small companies that have adopted e-business in an emerging Latin American country and found that the owners/shareholders play a central role in making decisions about the adoption of e-business as well as the main value delivered from using the internet was improved brand and/or product awareness [32]. Using EBMO, Kiani et al (2009) proposed causal loop diagram (CLD) and use it as a useful tool to capture the structure of e-business systems in order to achieve a better understanding of an e-business model.…”
Section: E-business Model Ontology (Ebmo)mentioning
confidence: 99%
“…the internet and email (Dobele, Toleman, & Beverland, 2005;Zilber & Braz de Araújo, 2012). These features make EM ideal for startups.…”
Section: Introductionmentioning
confidence: 99%